Role of Antimicrobial Peptides in Treatment and Prevention of Mycobacterium Tuberculosis: A Review - Mehta, Kanchan; Sharma, Prince; Shama, Mujawar *; Vyas, Ashish (Springer, 2022)
Tuberculosis (TB) is one of the leading cause of death worldwide, and the world is fighting with this global health emergency from the past 25 year. The current clinical interventions for the management of TB face a number of inherent challenges which includes low patient compliance due to the long therapy regimen, and emerging antimicrobial resistance. Therefore, there is an unmet need of new anti-TB therapeutic agent with enhanced safety profile, which can reduce the duration of therapy, enhanced bioavailability and efficacy against drug resistant forms of TB. Bacteriocins or anti microbial peptides (AMPs) occurring in microbes, human beings and other life forms have been investigated as host defense peptides. Structurally AMPs are short and ionized and play crucial role in innate immunity of host. Some AMPs can kill microbial infections directly while others function indirectly by altering the host defense mechanisms. Amidst rising issue of antibiotic resistance, AMPs are being tested in clinical research as potential antibiotics and novel therapeutics to fight against infections and non-infectious diseases. Studies have also highlighted the ability of AMPs to act against the bacteria spreading tuberculosis. The present review provides information on antimicrobial peptides, highlights their biological role, classification and mode of action in treatment and prevention of tuberculosis. It further mentions the prospects and challenges of developing peptides for their therapeutic applications against mycobacterium tuberculosis.